2016
DOI: 10.1161/circgenetics.116.001396
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization Studies Do Not Support a Role for Vitamin D in Coronary Artery Disease

Abstract: Given this uncertainty, clinical practice guidelines do not support vitamin D supplementation for CAD risk reduction andBackground-Observational studies support a possible association between decreased vitamin D levels and risk of coronary artery disease (CAD); however, it remains unclear whether this relationship is causal. We aimed to evaluate whether genetically lowered vitamin D levels influence the risk of CAD using a Mendelian randomization approach. Methods and Results-In this 2-stage Mendelian randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 69 publications
(80 reference statements)
6
67
0
1
Order By: Relevance
“…The study findings suggested that associations between schizophrenia and 25-hydroxyvitamin D may not be causal, and, therefore the evidential basis for vitamin D supplementation as a candidate approach for preventing schizophrenia is weakened. Similarly, a recent extensive Mendelian randomization study provides no support for a causal role for 25-hydroxyvitamin D in the risk of coronary artery disease 55 . On the other hand, in this issue Ong and co-workers 56 found that genetically lowered 25-hydroxyvitamin D levels were associated with higher susceptibility to ovarian cancer.…”
Section: Combining Ms and Nmr And Notes On Replication And Causalitymentioning
confidence: 96%
“…The study findings suggested that associations between schizophrenia and 25-hydroxyvitamin D may not be causal, and, therefore the evidential basis for vitamin D supplementation as a candidate approach for preventing schizophrenia is weakened. Similarly, a recent extensive Mendelian randomization study provides no support for a causal role for 25-hydroxyvitamin D in the risk of coronary artery disease 55 . On the other hand, in this issue Ong and co-workers 56 found that genetically lowered 25-hydroxyvitamin D levels were associated with higher susceptibility to ovarian cancer.…”
Section: Combining Ms and Nmr And Notes On Replication And Causalitymentioning
confidence: 96%
“…With respect to hypertension, Vimaleswaran et al 66 found that increased vitamin D levels could reduce the risk of development of CVD, showing a causal relationship. 66 On the other hand, the results of MR studies have not demonstrated a causal relationship for diabetes mellitus 67 and CAD, 68 in which vitamin D deficiency appears to be a confounding factor.…”
Section: Genetic Factors Of Vitamin D and Its Implications In Cardiovmentioning
confidence: 99%
“…Our findings suggest that previously observed associations are very likely to be confounded by CHD risk factors and lifestyle variables associated with 25OHD. In support of this notion, by using Mendelian randomization approach and eliminating confounding, genetically determined 25OHD was not found to be associated with risk of incident CHD 21 or cardiovascular mortality 22 . Therefore, the causality and the effects of vitamin D supplement on CHD are yet to be clarified in ongoing and future randomized controlled trials.…”
Section: Discussionmentioning
confidence: 89%